(Reflected) Backward Stochastic Differential Equations and Contingent Claims - Michael Kohlmann (University of Konstanz, Center of Finance and Econometrics (CoFE), 1999)
We review the relations between adjoints of stochastic control problems with the derivative of the value function, and the latter with the value function of a stopping problem. These results are applied to the pricing of contingent claims.
urn:nbn:de:bsz:352-opus-3197
Keywords: 330; Analysis; Stochastischer Prozess; Kontrolltheorie; Suchtheorie; Optionspreistheorie; Black-Scholes-Modell; Theorie